Implementasi Pendidikan Multikultural Melalui Tradisi Perang Topat: Pembelajaran Toleransi dan Solidaritas Antaragama di Lombok - Ida Bagus Alit Arta Wiguna; I Putu Sriartha; Wayan Mudana; I Made Pageh (Widya Sandhi, 2026)
This article discusses the implementation of multicultural education in the tradition of the Topat War in Lombok, which involved Sasak Muslim and Balinese Hindu communities. The purpose of this study is to explore how the Topat War ritual functions as a means of teaching tolerance and interfaith solidarity in a multicultural society. The method used is a qualitative approach with interviews, participatory observation, and document analysis. The research findings show that the Topat Waris is not only a cultural ritual, but also a forum for multicultural education that strengthens interfaith relations through practices of cooperation and mutual respect. However, the application of these values to informal education is still limited. This article contributes by proposing a model of multicultural education based on local wisdom that can be applied in the formal education curriculum, connecting local traditions with social value-based education. The results of this study emphasize the importance of integrating multicultural education into the formal education system to create a more inclusive and harmonious society.